Quercetin Zinc and Iron Metal Complexes Protect against Sodium Arsenite Intoxication in the Hepato-Renal System of Wistar Rats via the Oxidative Stress Pathway - Oluwatoyin O. Ojo; Deborah I. Fatokun; Ikechukwu P. Ejidike; Rachel U. Awolope; Saheed O. Sanni (Journal of Toxicology)
Background. Chronic exposure to arsenic is a major health concern consequent upon generation of excessive reactive oxygen species. The safety of treatment with chelating agents has not been well established; therefore, there is a need for a paradigm shift in the approach to management of arsenic toxicity. Bioflavonoids are known to influence redox homeostasis in cells; the study therefore investigates the efficacy of quercetin and its zinc and iron metal complexes on sodium arsenite (NaAr)-intoxication in rats. Methods. Spectroscopic study of quercetin hydrate and its metal complexes was performed using UV-Vis and FT-IR spectrometer. Furthermore, twenty male Wistar rats were obtained and equally divided into four groups, treated orally and daily for 28 days with 10 mg/kg NaAr, 30 mg/kg quercetin, quercetin-zinc, and quercetin-iron separately. Five more rats were used as control. Plasmatic aspartate transferase (AST), alanine transferase (ALT), creatinine (CREA), and total protein (TP) were estimated. Levels of kidney and liver lipid peroxidation (LPO), glutathione (GSH), catalase (CAT), and glutathione-S-transferase (GST) were determined. Histology was used to view the lesions. Results. Treatment of arsenic-toxicity with quercetin and its complexes decreased the activities of ALT, AST, CREA, TP, CAT, and GST and concentration of LPO and GSH. Quercetin-zn treatment showed a better result than quercetin-iron in the liver. Histology results showed absence of lesions in quercetin zinc and iron treatment in both the kidney and the liver. Conclusion. Quercetin zinc and iron increased the bioavailability of quercetin and therefore could be relevant as adjuvants in arsenic poisoning.